Positive electrode active material for lithium secondary batteries

The positive electrode active material for lithium secondary batteries, featuring a layered rhombohedral structure and directed lithium ion diffusion paths, addresses the limitations of existing materials by enhancing energy density, thermal stability, and lifespan.

JP7648688B2Active Publication Date: 2025-03-18ECOPRO BM CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023120500
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2014-09-11
Filing Date
2023-07-25
Publication Date
2025-03-18
Estimated Expiration
2035-01-21

AI Technical Summary

Technical Problem

Existing lithium secondary battery positive electrode active materials face challenges with low energy density, limited thermal stability, and short lifetime performance, particularly due to structural instability and high cobalt content.

Method used

A positive electrode active material with a layered rhombohedral crystal structure and a specific lithium ion diffusion path direction within primary and secondary particles, enhancing lithium ion conductivity and structural stability.

Benefits of technology

The proposed solution significantly improves the capacity and lifetime characteristics of lithium secondary batteries by facilitating efficient lithium ion storage and release, while reducing electron transfer resistance and impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648688000003
    Figure 0007648688000003
  • Figure 0007648688000004
    Figure 0007648688000004
  • Figure 0007648688000005
    Figure 0007648688000005
Patent Text Reader

Abstract

To provide a lithium secondary battery cathode active material that not only exhibits high lithium ion conductivity due to a directional lithium ion diffusion path within the primary particles and secondary particles, but also has high lithium ion conductivity, and also improve the crystal structure that does not collapse easily, and the cycle characteristics.SOLUTION: The present invention relates to a lithium secondary battery cathode active material according to the present invention and a lithium secondary battery including the same, and more specifically, the present invention relates to a lithium secondary battery cathode active material in which lithium ion diffusion paths within primary particles and secondary particles are formed with specific directionality.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material for a lithium secondary battery and a lithium secondary battery including the same, and more particularly, to a positive electrode active material for a lithium secondary battery, characterized in that lithium ion diffusion paths in primary particles and secondary particles are formed with a specific direction, and a lithium secondary battery including the same. [Background technology]

[0002] Recently, interest in energy storage technology has been increasing. The fields of application have expanded to include mobile phones, camcorders, notebook computers, and even the energy of electric vehicles, and efforts in the research and development of electrochemical devices have been increasingly made. Electrochemical devices are the field that has attracted the most attention in this regard, and among them, the development of secondary batteries that can be charged and discharged is the focus of attention.

[0003] Among the secondary batteries currently in use, lithium-ion batteries, developed in the early 1990s, have been widely used as power sources for portable devices since their introduction in 1991 as small, lightweight, and large-capacity batteries. Lithium secondary batteries have been in the spotlight due to their advantages of higher operating voltage and significantly higher energy density compared to conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries. They are particularly widely used in medium- and large-sized batteries of kWh class or higher used in electric vehicles and energy storage, and therefore require positive electrode active materials that have high capacity and can be used for long periods of time.

[0004] The application of high-capacity secondary batteries using spinel manganese oxide (LMO) and olivine-based cathode materials (LFP), which have excellent thermal stability, has limited commercialization due to low energy density, and there is an increasing need to apply high-capacity layered cathode materials to improve battery characteristics. Among the cathode materials for lithium secondary batteries, layered cathode materials can realize the highest capacity among the materials commercialized so far. LiCoO2, which is widely used in small IT devices such as smartphones, is not safe for use in medium- to large-sized batteries and has low capacity, and the main material, cobalt metal, has problems such as economical issues due to its high cost, limited resources due to reserves, and environmental regulations due to environmental pollution compared to other transition metals. LiNiO2, which has the same structure as LiCoO2, has been researched extensively due to its advantages of being relatively cheap and showing a high theoretical capacity of 200mAh / g. However, it has not been commercialized due to its poor safety and the problem of a rapid decrease in life performance due to structural instability generated during the manufacturing process.

[0005] In order to improve the shortcomings of LiNiO2, some attempts have been made to replace part of the nickel with transition metal elements, either to shift the heat generation start temperature slightly to the higher side or to prevent sudden heat generation. 1-x Co x In the case of LiNoO2 (x=0.1-0.3), the charge-discharge characteristics and life characteristics are relatively superior to those of LiNoO2, but the life performance is not sufficient. In addition, the composition of Li-Ni-Mn-based composite oxides partially substituted with Mn, which has excellent thermal safety at the Ni position, or Li-Ni-Mn-Co-based composite oxides substituted with Mn and Co, and the techniques related to their manufacture are also widely known. Recently, Japanese Patent Application No. 2000-227858 disclosed a new concept of a positive electrode active material in which a solid solution is made by uniformly dispersing Mn and Ni compounds at the atomic level, rather than the concept of partially substituting a transition metal in LiNiO2 or LiMnO2.

[0006] According to European Patent No. 0918041 and US Patent No. 6040090 regarding the composition of Li-Ni-Mn-Co composite oxides in which Ni is replaced by Mn and Co, LiNi 1-x Co x Mn y O2 (0 < y ≤ 0.3) has improved life performance and thermal stability compared to materials composed only of existing Ni and Co, but still could not solve the problem of the degradation of the thermal stability and life performance of the Ni system.

[0007] In order to eliminate such disadvantages, Korean Patent Application No. 10-2005-7007548 has proposed a patent for lithium transition metal oxides having a concentration gradient of metal composition. However, this method can achieve a high capacity by synthesizing the metal composition of the inner layer and the outer layer differently during synthesis, but the metal composition in the generated cathode active material does not change continuously and gradually. Although a gradual gradient of the metal composition can be formed by the heat treatment process, during long-term use, the interface between the inner layer and the outer layer acts as a resistance component, reducing the output and life performance. At a high heat treatment temperature of 850 °C or higher, almost no concentration gradient difference occurs due to the thermal diffusion of metal ions, so the effect of performance improvement is negligible. In addition, the powder synthesized by this invention does not use ammonia, which is a chelating agent, so the tap density of the powder is low and it is not suitable for use as a cathode active material for lithium secondary batteries.

Prior Art Documents

Patent Documents

[0008]

Patent Document 1

Patent Document 2

Disclosure of the Invention

Problems to be Solved by the Invention

[0009] In order to solve the above problems, the present invention aims to provide a new structure of a positive electrode active material for a lithium secondary battery, in which a lithium ion diffusion path in a primary particle and a secondary particle has a specific direction and can realize a long life. Another object of the present invention is to provide a lithium secondary battery including the positive electrode active material for lithium secondary batteries according to the present invention. [Means for solving the problem]

[0010] In order to solve the above-mentioned problems, the present invention provides a positive electrode active material having a layered structure containing a transition metal and having a rhombohedral crystal structure having an R3m structure as shown in Figs. 1 to 6, characterized in that the secondary particles are formed by agglomeration of primary particles, the aspect ratio of the primary particles is 1 or more, and the a-axis direction, which is the lithium ion diffusion path within the primary particles, is formed parallel to the long sides of the primary particles.

[0011] The positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the a-axis direction, which is the lithium ion diffusion path within the primary particle, is oriented toward the center of the secondary particle.

[0012] The positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the lithium ion diffusion path within the primary particle is formed with a direction toward the center of the entire particle, and the lithium ion diffusion path from the surface to the center of the secondary particle has a one-dimensional or two-dimensional tunnel structure.

[0013] The positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the lithium ion diffusion path in the primary particle forms an angle of ±40° or less with a connecting line connecting the surface of the secondary particle to the center of the secondary particle.

[0014] In addition, the positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the lithium ion diffusion path is an area occupied by primary particles forming an angle of ±40° with a connecting line connecting the surface of the secondary particle to the center of the secondary particle, or 10% or more of the area of ​​the secondary particle. That is, the positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the lithium ion diffusion path is formed in the primary particle while showing a direction toward the center of the secondary particle.

[0015] The positive electrode active material for a lithium secondary battery according to the present invention is characterized in that a lithium ion diffusion path within the primary particle is formed with a direction toward the center of the entire particle, and the lithium ion diffusion path from the surface to the center of the secondary particle has a one-dimensional or two-dimensional tunnel structure.

[0016] In the positive electrode active material for a lithium secondary battery according to the present invention, the primary particles have a high lithium ion conduction rate within the secondary particles due to the lithium ion diffusion pathway, and exhibit high lithium ion conductivity, as well as improved cycle characteristics due to the crystal structure being less likely to collapse even after repeated charging and discharging. That is, the positive electrode active material for a lithium secondary battery according to the present invention has low charge transfer resistance, diffusion, migration and convection between the active material particles and the lithium ions or electrolyte due to the lithium ion diffusion pathway formed in a one-dimensional tunnel structure in a linear pathway, and therefore the impedance inside the battery can be significantly reduced.

[0017] The positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the aspect ratio of the primary particles is 1 or more, and the lithium ion diffusion path within the primary particles is formed parallel to the major axis. That is, as described above, lithium ions are absorbed and desorbed within the primary particles during the charge and discharge process, and even when charge and discharge are continued, the lithium ion path is formed in the major axis direction, so that the portion of the crystal structure within the primary particles that is affected by the lithium absorption and desorption process is reduced, and as a result, structural stability is ensured by charge and discharge, and life characteristics are improved.

[0018] The positive electrode active material for a lithium secondary battery according to the present invention is characterized in that the aspect ratio is 1 or more, and the area occupied by primary particles in which the a-axis direction, which is a lithium ion diffusion path within the particle, is parallel to the long axis of the particle, is 40% or more of the area of ​​the secondary particles.

[0019] In the positive electrode active material for a lithium secondary battery according to the present invention, the secondary particles are represented by the following Chemical Formula 1, and are characterized in that the concentration of the transition metal is constant throughout the particle.

[0020] <Chemical formula 1> Li x Ni 1-a-b-c Co a Mn b Me c O 2-y X y (In the above chemical formula 1, 0.9≦x≦1.15.0≦a≦0.5, 0≦b≦0.65, 0≦c≦0.15, 0≦y≦0.1, Me is at least one element selected from the group consisting of Al, Mg, B, P, Ti, Si, Zr, Ba, and combinations thereof, and X is at least one atom or molecule selected from anions such as F, BO3, and PO4.) The present invention also provides a lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to the present invention. Effect of the Invention

[0021] In the positive electrode active material for a lithium secondary battery according to the present invention, the a-axis direction, which is the lithium ion diffusion path within the primary particles, is formed in a direction parallel to the long side of the primary particles and is formed with a direction toward the center of the secondary particles. Therefore, the absorption and release of lithium ions into the primary particles during charging and discharging is facilitated, and the capacity characteristics and life characteristics of a battery including the positive electrode active material for a lithium secondary battery according to the present invention are greatly improved. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 shows the rhombohedral structure. [Diagram 2] FIG. 2 shows SEM photographs of the positive electrode active material particles produced in Examples 1 to 6 and Comparative Examples 1 and 2 of the present invention. [Diagram 3] FIG. 3 shows the results of measuring SEM photographs of the fracture surfaces of the positive electrode active material particles produced in Examples 1 to 6 and Comparative Examples 1 and 2 of the present invention. [Figure 4] FIG. 4 shows the results of measuring the shape and structure of primary particles in the particles in Example 4 of the present invention using a TEM. [Diagram 5] FIG. 5 shows the results of measuring the shape and structure of primary particles in the particle of Comparative Example 1 of the present invention using a TEM. [Figure 6] FIG. 6 shows a schematic diagram of a cross section of a positive electrode active material particle of the present invention, a primary particle, and a lithium ion diffusion path. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0024] <Example 1> After adding 20 L of distilled water and 1000 g of ammonia as a chelating agent to a coprecipitation reactor (volume 100 L, rotary motor output 80 W or more), the temperature inside the reactor was maintained at 48° C. and the motor was stirred at 350 rpm. Nitrogen gas was continuously supplied to the reaction tank at a flow rate of 3 L / min.

[0025] A 2.5M concentration precursor aqueous solution, in which nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 1:1:1, was continuously fed into the reactor at 3.25 L / hr, and a 28% concentration ammonia aqueous solution was continuously fed at 0.15 L / hr. In addition, to adjust the pH, a 25% concentration sodium hydroxide aqueous solution was fed at 0.835 L / hr, and the pH was adjusted to 11.5, and the solution was continuously fed to the liquid surface in the reactor. The reaction solution temperature was maintained at 48°C to 50°C, and a 25% concentration sodium hydroxide aqueous solution was added to adjust the pH of the reaction solution to 11.5 to form metal hydroxide particles. After the reaction was completed, a spherical nickel manganese cobalt composite hydroxide precipitate was obtained from the co-precipitation reactor.

[0026] The precipitated composite metal hydroxide was filtered, washed with water, and then dried in a hot air dryer at 100° C. for 12 hours (Ni 0.33 Co 0.33 Mn 0.33 A precursor powder in the form of a metal composite hydroxide having the composition:

[0027] The metal composite hydroxide and lithium carbonate (Li2CO3) are mixed in a molar ratio of 1:1.00 to 1.10, and then fired at a temperature of 700°C to 1000°C for 10 to 20 hours at a heating rate of 2°C / min to form Li(Ni 0.33 Co 0.33 Mn 0.33 )O2 positive electrode active material powder was obtained.

[0028] <Example 2> The composition of the positive electrode is Li(Ni 0.5 Co 0.2 Mn 0.3 A positive electrode was prepared in the same manner as in Example 1, except that the molar ratio of nickel sulfate, cobalt sulfate, and manganese sulfate was adjusted so that the positive electrode potential was 0.01 to 0.02.

[0029] <Example 3> The composition of the positive electrode is Li(Ni 0.7 Co 0.2 Mn 0.1A positive electrode was prepared in the same manner as in Example 1, except that the molar ratio of nickel sulfate, cobalt sulfate, and manganese sulfate was adjusted so that the cation exchange ratio was 0.01 and lithium hydroxide was used instead of lithium carbonate.

[0030] <Example 4> The composition of the positive electrode is Li(Ni 0.8 Co 0.1 Mn 0.1 A positive electrode was prepared in the same manner as in Example 1, except that the molar ratio of nickel sulfate, cobalt sulfate, and manganese sulfate was adjusted so that the positive electrode potential was 0.01 to 0.01.

[0031] <Example 5> The bulk composition of the positive electrode is Li(Ni 0.820 Co 0.145 Al 0.035 A positive electrode was prepared in the same manner as in Example 4, except that the molar ratio of nickel sulfate, cobalt sulfate, and manganese sulfate was adjusted so that the positive electrode potential was 0.01 to 0.01.

[0032] <Example 6> The positive electrode composition is Li(Ni 0.90 Co 0.07 Al 0.03 A positive electrode was prepared in the same manner as in Example 4, except that the molar ratio of nickel sulfate, cobalt sulfate, and manganese sulfate was adjusted so that the positive electrode potential was 0.01 to 0.01.

[0033] <Comparative Example 1> After adding 80 liters of distilled water and 1000g of ammonia as a chelating agent to a reactor with a capacity of 100L, the motor was set to 5000 rpm and stirred while maintaining the temperature in the reactor at 50±2°C. Nitrogen gas was continuously supplied to the reaction vessel at a flow rate of 3L / min. Next, a 1M concentration precursor aqueous solution in which nickel sulfate, cobalt sulfate, and manganese sulfate were mixed in a molar ratio of 8:1:1 was continuously fed into the reaction vessel at 6.5L / hr, and a 28% concentration aqueous ammonia solution was continuously fed into the reaction vessel at 0.6L / hr. In addition, a 25% concentration aqueous sodium hydroxide solution was supplied at 1.5-2.0L / hr to adjust the pH to 11-12, and continuously supplied to the liquid surface in the reaction vessel. The temperature of the reaction solution was maintained at 50±2°C, and a 25% concentration aqueous sodium hydroxide solution was added so that the pH of the reaction solution was maintained at 11-12 to form metal hydroxide particles. After 30 hours when the inside of the reactor had returned to normal, the hydroxide particles discharged from the overflow pipe were continuously collected, washed with water, and then dried in a hot air dryer at 100°C for 12 hours to obtain Li(Ni 0.8 Co 0.1 Mn 0.1 A precursor powder of a metal composite hydroxide having the composition ZnO(OH)2 was obtained.

[0034] The metal composite hydroxide and lithium hydroxide (LiOH.H2O) were mixed in a molar ratio of 1:1.00 to 1.10, and then heated at a temperature increasing rate of 2°C / min. The mixture was then heat-treated at 550°C for 10 hours, and then calcined at 750°C for 20 hours to obtain a positive electrode active material powder.

[0035] <Comparative Example 2> The synthesis was carried out in the same manner as in Comparative Example 1, except that a 1M precursor aqueous solution in which nickel sulfate, cobalt sulfate, and aluminum nitrate were mixed in a molar ratio of 81.5:15:3.5 was used.

[0036] <Experimental example: SEM photo measurement> The positive electrode active material particles and their fracture surfaces prepared in Examples 1 to 6 and Comparative Examples 1 and 2 were photographed using SEM, and the results are shown in FIGS.

[0037] It can be seen from FIG. 2 that the positive electrode active material particles produced in Examples 1 to 6 and Comparative Examples 1 and 2 of the present invention are spherical secondary particles formed by agglomeration of primary particles.

[0038] In FIG. 3, which is an SEM photograph of the fracture surface of a particle, it can be seen that in the particles produced in Examples 1 to 6 of the present invention, the aspect ratio of the primary particles is 1 or more, and the primary particles grow in the long axis direction with a directionality toward the center of the particle, whereas in the cases of Comparative Examples 1 and 2, the primary particles are nearly circular, and no directionality of the primary particles is observed inside the secondary particles.

[0039] <Experimental example: TEM photo measurement> The patterns and structures of the primary particles of Example 4 and Comparative Example 1 were measured using a TEM, and the results are shown in FIGS.

[0040] In FIG. 4, in the case of the particles prepared in Example 4 of the present invention, it can be seen that the a-axis direction, which is the lithium ion diffusion path in the primary particles, is formed in the long axis direction of the particles, and at the same time, the a-axis direction, which is the lithium ion diffusion path in the primary particles, shows a direction toward the center of the secondary particles.

[0041] In contrast, in the case of FIG. 5 which shows a TEM photograph of the particles produced in Comparative Example 1, it can be seen that not only is the a-axis direction, which is the lithium ion diffusion path, not pointing toward the center of the particle, but it is also not parallel to the long axis.

[0042] <Experimental example: Particle characteristic measurement>

[0043] [Table 1]

[0044] <Manufacturing example: Battery manufacturing> The positive electrode active materials prepared in Examples 1 to 6 and Comparative Examples 1 and 2 were mixed with Super-P as a conductive agent and polyvinylidene fluoride (PVdF) as a binder in a weight ratio of 92:5:3 to prepare a slurry. The slurry was uniformly coated on an aluminum foil having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0045] A coin-type battery was manufactured by a known manufacturing process using the positive electrode, lithium foil as a counter electrode, a porous polyethylene film (Celgard, LLC., Celgard 2300, thickness: 25 μm) as a separator, and a liquid electrolyte containing LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0046] <Experimental example: Measurement of battery characteristics> The initial capacity, initial efficiency, ratio characteristic, and life characteristic of the batteries prepared using the active materials prepared in Examples 1 to 6 and Comparative Examples 1 and 2 were measured, and the results are shown in Table 2 below.

[0047] It can be seen from Table 2 below that the battery characteristics including the active material prepared in the examples of the present invention are significantly improved compared to the comparative examples.

[0048] [Table 2] [Industrial Applicability]

[0049] As described above, in the positive electrode active material for lithium secondary batteries according to the present invention, the a-axis direction, which is the lithium ion diffusion path within the primary particles, is formed in a direction parallel to the long sides of the primary particles and is formed with a direction toward the center of the secondary particles. This facilitates the absorption and release of lithium ions into the primary particles during charging and discharging, and is very useful in that the capacity characteristics and life characteristics of a battery including the positive electrode active material for lithium secondary batteries according to the present invention are greatly improved. Below, embodiments of the present invention will be described. Article 1. A positive electrode active material having a layered structure containing a transition metal, It is a spherical secondary particle formed by agglomeration of primary particles, and the aspect ratio of the primary particles is 1 or more. A positive electrode active material for a lithium secondary battery, characterized in that a lithium ion diffusion path formed inside the primary particle having a layered structure measured by TEM is formed toward the center of the secondary particle. Article 2. Item 2. The positive electrode active material for a lithium secondary battery according to item 1, characterized in that the a-axis direction, which is the lithium ion diffusion path formed inside the primary particle as measured by TEM, shows a direction toward the center of the secondary particle. Article 3. Item 1. A positive electrode active material for a lithium secondary battery, characterized in that the lithium ion diffusion path formed inside the primary particle has a direction toward the center of the entire particle, and the lithium ion diffusion path from the surface to the center of the secondary particle has a one-dimensional or two-dimensional tunnel structure. Article 4. Item 2. The positive electrode active material for a lithium secondary battery according to item 1, characterized in that the a-axis direction, which is a lithium ion diffusion path formed inside the primary particle, forms an angle of within ±40° with a connecting line connecting the surface of the secondary particle to the center of the secondary particle. Article 5. 5. The positive electrode active material for a lithium secondary battery according to claim 4, characterized in that the area occupied by the primary particles, in which the lithium ion diffusion paths form an angle of ±40° or less with a connecting line connecting the surface of the secondary particle to the center of the secondary particle, is 10% or more of the area of ​​the secondary particles. Article 6. Item 2. The positive electrode active material for a lithium secondary battery according to item 1, characterized in that the aspect ratio of the primary particles is 1 or more, and the area of ​​the lithium ion diffusion paths formed inside the primary particles, which are parallel to the major axis of the primary particles, occupies 40% or more of the area of ​​the secondary particles. Article 7. The secondary particles are represented by the following chemical formula 1: <Chemical formula 1> Li x Ni1- a - b - c Co a Mn b Me c O2- y X y (In the above chemical formula 1, 0.9≦x≦1.15.0≦a≦0.5, 0≦b≦0.65, 0≦c≦0.15, 0≦y≦0.1, Me is at least one element selected from the group consisting of Al, Mg, B, P, Ti, Si, Zr, Ba and combinations thereof, and X is at least one element or molecule selected from anions such as F, BO3, and PO4.) Item 1. A positive electrode active material for a lithium secondary battery according to item 1, characterized in that the concentration of the transition metal is constant throughout the particle. Article 8. Item 8. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to any one of items 1 to 7. Further embodiments of the present invention are described below. Article A-1. A positive electrode active material having a layered structure containing a transition metal, It is a spherical secondary particle formed by agglomeration of primary particles, and the aspect ratio of the primary particles is 1 or more. A lithium ion diffusion path formed inside the primary particle having a layered structure measured by TEM is formed toward the center of the secondary particle, and The concentrations of all transition metals contained in the positive electrode active material among Ni, Co, and Mn are constant throughout the particle. A positive electrode active material for a lithium secondary battery. Article A-2. The positive electrode active material for a lithium secondary battery according to clause A-1, characterized in that the a-axis direction, which is a lithium ion diffusion path formed inside the primary particle as measured by TEM, shows a direction toward the center of the secondary particle. Article A-3. The positive electrode active material for lithium secondary batteries described in clause A-1, characterized in that the lithium ion diffusion path formed inside the primary particle is formed with a direction toward the center of the entire particle, and the lithium ion diffusion path from the surface to the center of the secondary particle has a one-dimensional or two-dimensional tunnel structure. Article A-4. The positive electrode active material for a lithium secondary battery according to clause A-1, characterized in that the a-axis direction, which is a lithium ion diffusion path formed inside the primary particle, forms an angle of within ±40° with a connecting line connecting the surface of the secondary particle to the center of the secondary particle. Article A-5. The positive electrode active material for a lithium secondary battery according to clause A-4, characterized in that the area occupied by the primary particles, in which the lithium ion diffusion paths form an angle of within ±40° with a connecting line connecting the surface of the secondary particle to the center of the secondary particle, is 10% or more of the area of ​​the secondary particles. Article A-6. The positive electrode active material for a lithium secondary battery according to clause A-1, characterized in that the aspect ratio of the primary particles is 1 or more, and the area of ​​the lithium ion diffusion paths formed inside the primary particles, which are parallel to the major axis of the primary particles, occupies 40% or more of the area of ​​the secondary particles. Article A-7. The secondary particles are represented by the following chemical formula 1: <Chemical formula 1> Li x Ni 1-a-b-c Co a Mn b Me c O2- y X y (In the above chemical formula 1, 0.9≦x≦1.15.0≦a≦0.5, 0≦b≦0.65, 0≦c≦0.15, 0≦y≦0.1, Me is at least one element selected from the group consisting of Al, Mg, B, P, Ti, Si, Zr, Ba and combinations thereof, and X is at least one element or molecule selected from anions such as F, BO3, and PO4.) The positive electrode active material for a lithium secondary battery according to item A-1, characterized in that the concentration of the transition metal is constant throughout the particle. Article A-8. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to any one of A-1 to A-7.

Claims

1. A positive electrode active material having a layered structure of a rhombohedral crystal structure of R3m structure containing a transition metal, They are spherical secondary particles formed by agglomeration of primary particles. an area occupied by the primary particles having an a-axis direction which is a lithium ion diffusion path formed inside the primary particles and forms an angle of ±40° or less with a connecting line connecting the surface of the secondary particle and the center of the secondary particle in a cross section passing through the center of the secondary particle is 10% or more of a cross-sectional area passing through the center of the secondary particle, The secondary particles are characterized in that the entire particles are represented by the following Chemical Formula 1: <Chemical formula 1> Li x Ni 1-a-b-c Co a Mn b Me c O 2-y X y (In the above formula 1, 0.9≦x≦1.15, 0≦a≦0.5, 0≦b≦0.1, 0≦c≦0.15, 0≦y≦0.1, Me is at least one element selected from the group consisting of Al, Mg, B, P, Ti, Si, Zr, Ba, and combinations thereof, and X is at least one element or molecule selected from the anions of F, BO3, and PO4.)

2. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the a-axis direction, which is a lithium ion diffusion path inside the primary particle, shows a direction toward the center of the secondary particle.

3. 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the a-axis direction, which is the lithium ion diffusion path inside the primary particle, is formed with a direction toward the center of the entire secondary particle, and the lithium ion diffusion path from the surface to the center of the secondary particle has a one-dimensional or two-dimensional tunnel structure.

4. in a cross section passing through the center of the secondary particle, an aspect ratio is greater than 1, and an area occupied by the primary particle in which an a-axis direction, which is a lithium ion diffusion path formed inside the primary particle, is parallel to a major axis of the primary particle is 40% or more of a cross-sectional area passing through the center of the secondary particle, 2. The positive electrode active material for a lithium secondary battery according to claim 1, wherein the aspect ratio means the major axis length / minor axis length.

5. A lithium secondary battery comprising the positive electrode active material for lithium secondary batteries according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Positive electrode active material for non-aqueous lithium secondary battery and the non-aqueous lithium secondary battery using the active material

    JP2002279985A

  • Manufacturing method of cathode active material for lithium-ion battery

    JP2014049410A

  • Method of manufacturing positive electrode active material for lithium ion battery

    JP2014067645A

  • Cathode active material for a lithium ion secondary battery and a lithium ion secondary battery

    US20140087265A1

  • Positive electrode active material precursor for lithium secondary battery, positive electrode active material manufactured by using thereof, and lithium secondary battery including same

    US20140158932A1